Behavioural Features of Various Social Groups on the Internet - Gerasimova, Galina I.; Gavrilova, Nadezhda Yu.; Medvedev, Pavel S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The objective of the article is to find an effective model for teaching children using modern educational technologies. Background: The relevance of the study is that the formation of communication in social networks is determined by the ability to search for strategies for social contacts. In this regard, a significant part of people uses a ready-made communicative model created on a technological basis in social networks. The issue of understanding the general structure of communication in the formation of the social structure of a person in adolescents remains debatable. Method: The article notes that the operation of social networks is governed by purely technical methods and technologies, which can be considered as prerequisites for the translation of such technologies into the space of social interactions. Results: The authors show that the possibility of a regulatory impact on adolescent behaviour fully meets the principles of organising network communities with an orientation on each person’s individual characteristics. Conclusion: The use of Internet technologies allows for the growth and timely development of communication technologies for the formation of a balanced personality in a globalised world.